The bilateral relationship between human capital investment and innovation in Jordan - Mohammad Alawamleh; Loiy Bani Ismail; Diana Aqeel; Kamal Jamal Alawamleh (Journal of Innovation and Entrepreneurship, 2019)
The purpose of this research is to investigate the relationship between innovation and human capital investment, and to show how the implementation of these two concepts leads to economic development. A case study was conducted in Jordan with one-to-one, in-depth expert interviews to obtain the information needed to answer the research questions; in addition, a focus group of ten final year undergraduate students (about to enter the educated workforce) experts offered their thoughts and ideas to identify how youth today relate to this research and its findings. The findings identified four main pillars required to support economic development and achieve a competitive advantage using the country's human capital: Habilitation, Opportunity, Power Distance, and Entrepreneurship (HOPE). The findings also indicated that Jordanian culture is highly germane to all four pillars, which can encourage innovative human capital and ensure economic development. This paper is important to the Jordanian community and the Arab world in general, which lacks awareness of the importance of human capital in socio-economic development; the study helps understand innovation and economic development in the region. This paper explores the relationship between innovation and human capital investment, and shows how this combination will lead to the development of Jordanian culture and the economy.
Keywords: 650; Human capital investment; Innovation; Economic development; Jordan; Culture